Biodegradation of mixed polycyclic aromatic hydrocarbons by pure and mixed cultures of biosurfactant producing thermophilic and thermo-tolerant bacteria - Mehetre, Gajanan T.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2019)
Applicability of thermophilic and thereto-tolerant microorganisms for biodegradation of polycyclic aromatic hydrocarbons (PAHs) with low water solubility is an interesting strategy for improving the biodegradation efficiency. In this study, we evaluated utility of thermophilic and thermo-tolerant bacteria isolated from Unkeshwar hot spring (India) for biodegradation of four different PAHs. Water samples were enriched in mineral salt medium (MSM) containing a mixture of four PAHs compounds (anthracene: ANT, fluorene: FLU, phenanthrenc: PHE and pyrene: PYR) at 37 degrees C and 50 degrees C. After growth based screening, four potent strains obtained which were identified as Aeribacillus pallidus (UCPS2), Bacillus axarquiensis (UCPD1), Bacillus siamensis (GHP76) and Bacillus subtilis subsp. inaquosorum (U277) based on the 16S rRNA gene sequence analysis. Degradation of mixed PAH compounds was evaluated by pure as well as mixed cultures under shake flask conditions using MSM supplemented with 200 mg/L concentration of PAHs (50 mg/L of each compound) for 15 days at 37 degrees C and 50 degrees C. A relatively higher degradation of ANT (92% - 96%), FLU (83% - 86%), PHE (16% - 54%) and PYR (51% - 71%) was achieved at 50 degrees C by Aeribacillus sp. (UCPS2) and mixed culture. Furthermore, crude oil was used as a substrate to study the degradation of same PAHs using these organisms which also revealed with similar results with the higher degradation at 50 degrees C. Interestingly, PAH-degrading strains were also positive for biosurfactant production. Biosurfactants were identified as the variants of surfactins (lipopeptide biosurfactants) based on analytical tools and phylogenetic analysis of the surfactin genes. Overall, this study has shown that hot spring microbes may have a potential for PAHs degradation and also biosurfactant production at a higher temperature, which could provide a novel perspective for removal of PAHs residues from oil contaminated sites. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biodegradation; Biosurfactants; Crude oil; Mixed culture; PAHs; Thermophiles

Bacterial biofilm formation using PCL/curcumin electrospun fibers and its potential use for biotechnological applications - Pompa-Monroy, Daniella Alejandra; Figueroa-Marchant, Paulina Guadalupe; Dastager, Syed G.; Thorat, Meghana Namdeo; Iglesias, Ana Leticia; Miranda-Soto, Valentin; Perez-Gonzalez, Graciela Lizeth; Villarreal-Gomez, Luis Jesus (Materials, 2020)
Electrospun nanofibers are used for many applications due to their large surface area, mechanical properties, and bioactivity. Bacterial biofilms are the cause of numerous problems in biomedical devices and in the food industry. On the other hand, these bacterial biofilms can produce interesting metabolites. Hence, the objective of this study is to evaluate the efficiency of poly (x190;- caprolactone)/Curcumin (PCL/CUR) nanofibers to promote bacterial biofilm formation. These scaffolds were characterized by scanning electron microscopy (SEM), which showed homogeneous fibers with diameters between 441-557 nm; thermogravimetric analysis and differential scanning calorimetry (TGA and DSC) demonstrated high temperature resilience with degradation temperatures over >350 degrees C; FTIR and H-1-NMR serve as evidence of CUR incorporation in the PCL fibers. PCL/CUR scaffolds successfully promoted the formation of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa biofilms. These results will be valuable in the study of controlled harvesting of pathogenic biofilms as well as in metabolites production for biotechnological purposes.
Keywords: Bacteria; curcumin; electrospinning; Escherichia coli; Pseudomona aeruginosa; Staphylococcus aureus

Bacterial nanocellulose: a versatile biopolymer production using a cost-effective wooden disc based rotary reactor - Jagtap, Ashish; Dastager, Syed G. (Biopolymers, 2024)
Bacterial nanocellulose (BNC) has various unique qualities, including high mechanical strength, crystallinity, and high water-holding capacity, which makes it appropriate for a wide range of industrial applications. But its lower yield coupled with its high production cost creates a barrier to its usage. In this study, we have demonstrated the better yield of BNC from an indigenous strain Komagataeibacter rhaeticus MCC-0157 using a rotary disc bioreactor (RDB) having a wooden disc. The RDB was optimized based on the type of disc material, distance between the disc, and rotation speed to get the highest yield of 13.0 g/L dry material using Hestrin-Schramm (H-S) medium. Further, the bioreactor was compared for the BNC production using reported medium, which is used for static condition; the RDB showed up to fivefold increase in comparison with the static condition reported. Komagataeibacter rhaeticus MCC-0157 was previously reported to be one of the highest BNC producing stains, with 8.37 g/L of dry yield in static condition in 15 days incubation. The designed RDB demonstrated 13.0 g/L dry yield of BNC in just 5 days. Other characteristics of BNC remain same as compared with static BNC production, although the difference in the crystallinity index was observed in RDB (84.44%) in comparison with static (89.74%). For the first time, wooden disc was used for rotary bioreactor approach, which demonstrated higher yield of BNC in lesser time and can be further used for sustainable production of BNC at the industrial level. image
Keywords: bacterial nanocellulose; rotary reactor; Sustainability; wooden disc

Bacterial nanocellulose (BNC) produced from sorbitol as a sustainable nano-filter for oil-water separation - Jagtap, Ashish; Krushnatray, Ajinkya; Dastager, Syed G. (International Journal of Biological Macromolecules, 2025)
Oil spillage is one of the serious problems for sustainable environment. Bacterial nanocellulose (BNC), a hydrophilic and highly porous material holds a promising material for oil-water separation from contaminants. In the present work, a hydrophilic BNC produced from a sorbitol as the carbon source demonstrated the unique porous symmetrical arrangement having an oleophilic property. The BNC membrane obtained showed the highest water holding capacity (WHC) of approximate to 147 gg 1 . The Brunauer-Emmett-Teller (BET) analysis of BNC revealed the unique characteristics of isothermic patterns, having macro sized pores with diameter of 121.3 nm and surface area of 40.6m2/g, which plays a vital role in separation of oil from water by allowing passage of only water through it. The separation efficiency of BNC membrane produced after 5th day of incubation has showed 99.0 % oil removal compared to 10 and 15th day incubated BNC membranes. a CFD model to investigate the possibilities of BNC membranes and clarify the dynamics of oil-water separation. The nanostructured network of BNC offers a tortuous path for oil molecules while allowing rapid permeation of water, leading to high separation selectivity and flux. Although BNC has been previously studied for oil water separation, this study provides new insights into the use of wet BNC membranes into its pristine state with sorbitol as carbon source for this application.
Keywords: bacterial nanocellulose; Macro porous; Oil-water separation; Sorbitol